Socio-Economic Space and Territorial Development of the North and the Arctic of Russia - Lazhentsev, Vitaly Nikolaevich (Economy of Regions, 2018)
The spatial and territorial development of Russia was explored by many groups of geographers, historians and economists within the framework of academic programs. I interpret such development as economic and geographic activity covering regional statistics, geo-informatics, spatial planning and design as well as geographical review. This approach corresponds to one of the general directions of fundamental research of RAS «Development of the strategy of the transformation of the socioeconomic space and territorial development of Russia». My northern research, since 2010, has become an integral part of the RAS programmes «Fundamental issues of spatial development of the Russian Federation: the interdisciplinary synthesis». Its conceptual foundations were formulated by Academician A. G. Granberg and «The role of the space in the modernization of Russia: natural and socio-economic potential» (supervisor, Academician V M. Kotlyakov). At first, I consider the following problems of the North: the North and Russia’s internal market, modernization of the Northern households, scientific and technical preparation of the projects for the upcoming development of the Arctic. Further, I give the scientific explanation of the issues of socio-economic development. They are due to the poor state of the spatial organization of national economy in Russian Federation and the underestimation of the economic systems formed in the Northern and Arctic regions. These systems are divided into three types: territorial and economic complexes, certain centers (industrial periphery), the periphery of rural type. Complexes concentrate about 60 % of labour potential of the North, the industrial periphery - 15 % and rural - 25 %. They have different directions for the economic modernization and on the condition of this potential realization can ensure long-term sustainable development to the Northern regions. The Arctic vector of natural resource economy can succeed if its scientific and technical preparation is considered as an independent and priority direction of appropriate programs and projects. In fact, the science plays a pioneering role in the development of territories with an extreme environment.